Living Qur’an dalam Tradisi Batumbang di Kuburan Pada Masyarakat Desa Satiruk Kotawaringin Timur - Nafi Nur Ramadhan; Akhmad Dasuki; Munirah Munirah (Jayapangus Press, 2025)
The practice of religious traditions and rituals in graveyards often causes controversy because some people consider them to be elements of shirk. However, these traditions remain alive, as seen in the batumbang ritual in Satiruk Village. This study aims to analyze how the Qur'an is brought to life and applied in local culture through the batumbang tradition`, as well as to understand the integration of Islamic teachings in local cultural practices. This study uses the living Qur'an theory and Emile Durkheim's Cultural Paradigm theory as its analytical framework. The method used is qualitative with a field research approach that includes observation, in-depth interviews, and document analysis. The results show that the batumbang tradition serves as an expression of the community's gratitude for the fulfillment of their vows by combining Islamic teachings, such as the recitation of Surah Al-Fatihah and Surah Yasin, with local cultural practices. In the context of Durkheim's Cultural Paradigm theory, this ritual reflects four main pillars, namely sacredness as seen in the ritual at the grave of a religious figure, role classification in the ritual, rites reflected in the recitation of Surah Yasin, and solidarity formed through togetherness in prayer and food sharing. The batumbang tradition also reflects the application of the living Qur'an, in which the teachings of the Qur'an are translated into social practices that strengthen social bonds and religious understanding among the local community. This study concludes that the batumbang tradition illustrates the synergy between Islamic teachings and local culture, which reinforce each other.